Detachable Cheek Plumper Using Orthodontic Lingual Button For Improved Denture Esthetics: A Clinical Technique - Rathee, M; Alam, M; Jain, P; Kaur, M; Divakar, S; Chahal, S; Singh, S; Tomar, SS (Journal of Nepalese Prosthodontic Society, 2022)
Following loss of teeth and residual ridge resorption, facial esthetics is highly affected. The rehabilitation of lost structures should not be only aimed at replacing the lost teeth but facial changes associated with the edentulism should also be addressed. Objective of this technique article was aimed to improvise the excessive shrunken cheek appearance through fabrication of customized detachable cheek plumper. In this article, a novel, simple and easy technique has been described to fabricate a detachable cheek plumper for the management of shrunken cheek appearance using modified orthodontic lingual button and elastic tooth separator. Following fabrication of detachable cheek plumper and insertion, shrunken cheek appearance was improved and overall facial esthetic was enhanced. Cheek plumpers are simple to make and offer a noninvasive and cost-effective option for patients with sunken cheeks who want to improve their facial look. Patient’s aesthetics and psychological well-being benefit from this treatment. The use of detachable cheek plumper improves patient comfort, resulting in higher acceptance of the prosthesis.